Das Ende einer politischen Geographie ohne sozialgeographische Bindung - Schöller, Peter (ERDKUNDE, 1958)
Otto Maulls Politische Geographie published in 1956 is a retrogressive step in a number of ways compared to this book of 1925 with the same title, which was a systematic treatment of this topic. It is out of date in its basic concept, and scientifically untenable; the number of mistakes is great, that of half-truths unmeasurable; political resentment is dangerously linked with misjudgements and geopolitical prognoses. The doctrine of the state as a Space organism and its application to the world situation of the present, though historically based, but used purely from the aspect of power politics, forces the facts into a strait-jacket rather than helps towards an understanding. This book means the end of a political geography without ties with social geography. For the future work in this field the breakdown of this outdated kind of political geography can do nothing but good. What matters today is a deepened insight into the interrelations between economic structure, social structure, type of state and further also an understanding of the three dimensional circulations within the countries. The foremost task is to grasp analytically within a dynamic region - a concept freed from the aspect of visibility - the forces which shape politics and those which emanate from the state, and to integrate them into a cultural geographical synthesis.